2011
DOI: 10.1002/pola.24674
|View full text |Cite
|
Sign up to set email alerts
|

A fully biobased epoxy resin from vegetable oils: From the synthesis of the precursors by thiol‐ene reaction to the study of the final material

Abstract: A novel vegetable oil-based polyamine issued from grapeseed oil (GSO) was prepared using cysteamine chloride (CAHC) by thiol-ene coupling (TEC). The structure of the polyamine oil (AGSO) was carefully examined using a large range of chemical analyses (FTIR, 1 H NMR and 13 C NMR, LC-MS…). The effects of the amination of GSO on the vegetable oil properties were also studied using viscosimetry. Then, AGSO was employed as a novel curing agent for bio-based epoxy resin. The thermal crosslinking reaction between AGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(153 citation statements)
references
References 56 publications
3
148
0
2
Order By: Relevance
“…Among a large variety of biomasses, vegetable oils are most sufficiently studied starting materials to synthesize epoxy resins (epoxied vegetable oils). Combination of epoxied vegetable oils and vegetable oil-based curing agents results in the total biobased epoxy systems taking the advantage of high biomass contents [11]. Moreover, Mija et al [12] found that a suitable acid anhydride with a suitable catalysis under optimized curing condition was found to be able to endow epoxidized linseed oils with better properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among a large variety of biomasses, vegetable oils are most sufficiently studied starting materials to synthesize epoxy resins (epoxied vegetable oils). Combination of epoxied vegetable oils and vegetable oil-based curing agents results in the total biobased epoxy systems taking the advantage of high biomass contents [11]. Moreover, Mija et al [12] found that a suitable acid anhydride with a suitable catalysis under optimized curing condition was found to be able to endow epoxidized linseed oils with better properties.…”
Section: Introductionmentioning
confidence: 99%
“…EVO are employed as surface-active substances, lubricating materials, alternative fuel, raw materials for the production of coatings, inks, plasticizers, lubricants [4]. Epoxidized soybean oil (ESO) and epoxidized linseed oil are commercially available as stabilizers and plasticizers for PVC and modifiers for coatings [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that triglycerides contain double bonds, the indicated compounds have low reactivity, which is why the crosslinked polymers based on them can be obtained at limited conditions of reaction [4,5,8]. If the structure of triglyceride includes aliphatic chains, the synthesized materials do not possess required rigidity and strength.…”
Section: Introductionmentioning
confidence: 99%
“…The resin obtained exhibited a Tg of 328C. Other amines were designed from vegetable oils, by dimerization followed by amidification (Fomina, 2010), by thiol-ene coupling (Stemmelen et al, 2011), by nitrile synthesis (Dubois, Gillet, 2008) or by a 3 step reaction from epoxydized oil (Zao et al, 2008). But our method allows to synthesize fatty amidoamine in a one-step reaction.…”
Section: Polyamines Synthesized By Amidification Reactionmentioning
confidence: 99%